Pengembangan Sistem Informasi Pengolahan Data Pegawai di Camat Peukan Baro Kabupaten Pidie Menggunakan Visual Basic 6.0 - Iqbal, Taufiq; Ismail; Ahmad, Lukman (Jurnal Manajemen Sistem Informasi (JMASIF), 2023)
This research aims to develop an employee data management information system at the Camat Peukan Baro office in Pidie Regency, which was previously done manually using applications such as Microsoft Word and Microsoft Excel. The newly developed system utilizes Microsoft Visual Basic 6.0 and Microsoft Access 2007, aiming to improve efficiency, accuracy, and speed in managing employee data. The methodology employed in this research includes system requirements analysis, system design, implementation, as well as system testing and evaluation. The system design process involves the creation of a database and user interface to facilitate employees in inputting and managing employee data. After the system implementation, testing is conducted to ensure that the system functions according to user requirements. The test results show that the new system significantly speeds up the data management process and reduces the likelihood of errors. The implementation of this information system is expected to streamline employee data administration at Camat Peukan Baro, enhancing data transparency and accuracy.